2019
DOI: 10.3390/ijms20225551
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin III Induces JAK2/STAT3 Leading to IL-6 Production in Rat Vascular Smooth Muscle Cells

Abstract: The Janus kinase-2/ signal transducer and activators of transcription-3 (JAK2/STAT3) pathway and interleukin-6 (IL-6) are pleiotropic signal transduction systems that are responsible for induction of many cytokines and growth factors. It is unknown whether the renin angiotensin aldosterone system (RAAS) peptide, angiotensin (Ang) III induces JAK2/STAT3 and IL-6 in vascular smooth muscle cells (VSMCs). Thus, the purpose of this study was to investigate whether Ang III induces the JAK2/STAT3 pathway leading to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This data suggests that anti-angiogenic effects mediated by Ang 1–7 could be dramatically attenuated, thus promoting further vessel development ( van Esch et al, 2008 ; Pei et al, 2016 ; Touyz and Montezano, 2018 ). Furthermore, it has been shown that AngIII pro-angiogenic effects are mediated by both AT1 and AT2 receptors binding ( Kawasaki et al, 1988 ; Cheng et al, 1994 ; Del Borgo et al, 2015 ; Alanazi and Clark, 2019 , 2020 ). Therefore, our data suggests that in the context of glucocorticoid stimulation due to chronic stress, the upregulation of several RAS components could be a major player in the increased renal vascular density via the overstimulation of the AT1 and AT2 receptors along with the reduced Ang 1–7 anti-angiogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests that anti-angiogenic effects mediated by Ang 1–7 could be dramatically attenuated, thus promoting further vessel development ( van Esch et al, 2008 ; Pei et al, 2016 ; Touyz and Montezano, 2018 ). Furthermore, it has been shown that AngIII pro-angiogenic effects are mediated by both AT1 and AT2 receptors binding ( Kawasaki et al, 1988 ; Cheng et al, 1994 ; Del Borgo et al, 2015 ; Alanazi and Clark, 2019 , 2020 ). Therefore, our data suggests that in the context of glucocorticoid stimulation due to chronic stress, the upregulation of several RAS components could be a major player in the increased renal vascular density via the overstimulation of the AT1 and AT2 receptors along with the reduced Ang 1–7 anti-angiogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK2/STAT3 pathway serves as a crucial downstream mediator for the signal transduction of a variety of hormones, cytokines, and growth factors 29 . It has been shown that JAK activation is involved in the proliferation of VSMCs, and Ang II through the JAK2/STAT3 pathway increases nitroxidative stress, which contributes to the hyperproliferation of VSMC 30,31 . The study revealed that 7‐ketocholesterol upregulated profilin‐1 expression in aortic endothelial cells by activating the OSBP1/STAT3 pathway 32 .…”
Section: Discussionmentioning
confidence: 96%
“…The pathophysiology of EH is a highly complex mechanism. Multiple signaling-associated pathways, including the JAK2/STAT3 pathway, play a significant function in the pathophysiology of EH ( Mladěnka et al, 2018 ; Alanazi and Clark, 2019 ). Bioavailability of quercetin has been found to be involved in anti-hypertension, specially EH.…”
Section: Discussionmentioning
confidence: 99%